Personality determinants of the traffic accident risk of drivers – a review of selected studies and a proposal for their interpretation within the circumplex of personality metatraits model - Gasiul, Henryk; Strus, Włodzimierz (Studia Psychologica: Theoria et praxis, 2020)
The purpose of this article is a review of studies on the personality factors in risky behaviors, susceptibility to fatigue and the rate of accidents in motor vehicle traffic. We are also attempting to frame these factors within the Circumplex of Personality Metatraits (CPM) model. A large number of studies and a variety of models and measures used made the integration of the gathered empirical data difficult. While it initially appeared that the Five Factor Model of personality (also known as the Big Five model) could be used as the synthetizing function, most recent studies and analyses indicate that its potential in that respect is limited, especially when compared to models taking into account higher order factors (metatraits) of personality. One of such models is CPM and the authors propose its use as an integrating model for the existing variety of studies on the personality factors in risky behaviors, fatigue and traffic accidents. The analyses presented in the article have shown that 3 metatraits are important in this context: Delta-minus/Sensation Seeking, Alpha-minus/Disinhibition and Gamma-minus/Disharmony. We also show that a predictive model based on these broad personality variables is both parsimonious and relevant.